A continuous flow-chamber to study prey preferences of Golden Perch (Macquaria amhigua Richardson) larvae - Arumugam, Phillip T. (Springer-Verlag, 1990)

(untitled)
This paper describes the use of a continuous-flow chamber for maintaining small and fragile fish larvae and their prey in a healthy state and under suitable conditions over a 24 h period for studies on prey preferences. Survival of golden perch (Macquaria ambigua Richardson) larvae and prey was high and ten replicates on food preferences were carried out simultaneously. The larvae preferred small Daphnia carinata King (780–860 µm) over larger ones (2000–3120 and 3680–5440 µm) and preferred cladocerans (Daphnia carinata King and Moina micrura Kurz) over calanoids (Boeckella de Guerne & Richard). The chamber is also suitable for studies on feeding behaviour and diet requirements of fish larvae.